The importance of reciprocity: Investigating individual differences underlying conditional cooperation - Léon Bartosch; Dorothee Mischkowski (Max Planck Institute for Research on Collective Goods, 2023)
Several models of social preferences have been developed at the intersection of social psychology and behavioral economics, such as social value orientation (SVO) and conditional cooperation. Whereas SVO is well researched in its dispositional and situational correlates, we aim to locate conditional cooperation within the HEXACO personality model, particularly expecting a relation to reactive vs. active prosociality (i.e., Agreeableness vs. Honesty-Humility). Contrary to our expectations, however, in two preregistered, incentivized studies (n total = 521) conditional cooperation was neither related to Agreeableness nor to Honesty-Humility. When investigating the relation between SVO and conditional cooperation, we conceptually replicate a positive relation between both (pro-)social preferences. Surprisingly, while prosocials coincide with conditional cooperators, even most individualists who maximize their outcome in unilateral giving turn to conditionally cooperative behavior in strategic interactions. This underlines the importance of shaping situations as reciprocal acts to elicit cooperative behavior from originally self-interested individuals.
hdl:21.11116/0000-000C-47B9-4
Keywords: 330; Conditional Cooperation; Social Value Orientation; Basic Personality Traits; HEXACO; Reciprocity